Five new Brazilian species of Eugenia (Myrtaceae) - Sobral, Marcos; Faria, Jair E.q.; Coutinho, Karoline (Phytotaxa, 2018)
Five species of Eugenia are described, illustrated and compared with related species. Eugenia anisomischa, from the state of Bahia, is morphologically related to Eugenia candolleana, from which it differs by the pilose leaves and flowers; Eugenia cerradensis, from the states of Goiás and Mato Grosso, E. pantanalensis, from the states of Mato Grosso and Mato Grosso do Sul, and E. tingui, from the state of Rio Grande do Norte, are morphologically related to E. stictopetala, differing largely by its indumentum, larger flowers and wider leaves, respectively; E. zigzag, from the state of Bahia, is distinct from all other Brazilian species by its zigzag branching pattern.